The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.20527/jetall.v5i2.13462
|View full text |Cite
|
Sign up to set email alerts
|

Higher-Order Thinking Skills on Teachers-Made Tests by English Teachers of a Senior High School in Bengkulu City

Abstract: The objectives of this study are to investigate the composition of Higher Order Thinking Skills (HOTS) on the English teacher-made test based on the revised Bloom’s taxonomy and investigating the quality of the teacher-made tests viewed from the composition of HOTS. This study was a content analysis that used a triangulation design: data transformation model mixed method approach. The data of this study were teacher-made test sets that consisted of 136 questions. The data were analyzed by understanding the ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…This trend aligns with prior research, such as Wisrance and Semiun (2020), which observed a scarcity of HOTS in teacher-crafted tests at the junior high school level, with a focus primarily on remembering (C1) and understanding (C2) according to the Revised Bloom's Taxonomy. Similar findings were reported by Pratiwi et al (2019), Dewi & Sukarni (2020), Syahdanis et al (2021), Utami et al (2019), andApriana et al (2022), highlighting a preference among senior high school English teachers in Indonesia for LOTS questions, which do not adequately encourage critical thinking or reasoning skills among students.…”
Section: C5 (Evaluating)supporting
confidence: 79%
See 1 more Smart Citation
“…This trend aligns with prior research, such as Wisrance and Semiun (2020), which observed a scarcity of HOTS in teacher-crafted tests at the junior high school level, with a focus primarily on remembering (C1) and understanding (C2) according to the Revised Bloom's Taxonomy. Similar findings were reported by Pratiwi et al (2019), Dewi & Sukarni (2020), Syahdanis et al (2021), Utami et al (2019), andApriana et al (2022), highlighting a preference among senior high school English teachers in Indonesia for LOTS questions, which do not adequately encourage critical thinking or reasoning skills among students.…”
Section: C5 (Evaluating)supporting
confidence: 79%
“…Despite the emphasis on HOTS in policy and curriculum, studies on its application in English National Examinations and teacher-made tests reveal a significant underrepresentation of HOTS in assessment items. Findings demonstrate a prevalence of LOTS in the assessments, with a minimal presence of items evaluating higher cognitive levels, underscoring the need for enhanced teacher training and competency in creating HOTS-based assessment items (Narwianta et al, 2019;Putra and Abdullah, 2019;Widyaningsih and Septiana, 2019;Ilham et al, 2020;Pratiwi et al, 2019;Utami et al, 2019;Dewi & Sukarni, 2020;Wisrance and Semiun, 2020;Syahdanis et al, 2021;Apriana et al, 2022;Febriyana & Harjanto, 2023).…”
Section: Introductionmentioning
confidence: 96%